(untitled) (Perner’s Contacts, 2011)
This paper is about new scientific research project: Centre of excellence for Air Transport -ITMS 26220120065, which is realized at Air Transport Department of University of Žilina in cooperation with Flight Training Organization (FTO) – Air School of the University of Zilina. This project is co financed from sources of EU, which supports research activities in Slovak Republic. The project focuses on the impact of air transport on environment, including photogrammetry and surveillance of electromagnetic compatibility of monitoring of radio navigation and radio communication equipments.